Counteracting unemployment in crises : non-linear effects of short-time work policy - Gehrke, Britta (Nürnberg, 2017)
"Short-time work is a labor market policy that subsidizes working time reductions among firms in financial difficulty in order to prevent layoffs and stabilize employment. Many OECD countries have used this policy in the Great Recession, for example. This paper shows that the effects of discretionary short-time work are strongly time dependent and non-linear over the business cycle: it may save up to 0.8 jobs per short-time worker in deep economic crises. In contrast, in normal times and expansions, the effects are smaller and may even turn negative. Our results demonstrate that the policy becomes more efficient as the recession deepens. We disentangle discretionary short-time work from automatic stabilization in German data and estimate time-varying employment effects using a smooth transition VAR."